ANALISIS KELAYAKAN BUDIDAYA IKAN TUNA SIRIP KUNING DENGAN KERAMBA JARING APUNG OFFSHORE DI PERAIRAN SANGIHE UNTUK MENINGKATKAN NILAI EKSPOR - Zahrani Putri Amalia; Dian Ajeng Rachmawati; Wanda An Nisaa’ Awwalia; Maulidina Putri Rakhmawati (Jurnal Cakrawala Maritim, 2023)
Yellowfin tuna is one of the high value fishery commodities, but has a low export value. One solution to increase the value of these exports is by raising tuna in offshore circular floating net cages (KJA) to produce high quality yellowfin tuna. This study aims to analyze whether the Sangihe waters meet the criteria for the location of the offshore floating net cage (KJA), which is carried out by determining the location parameters of the offshore marine cage using descriptive analysis and literature study. Based on the results of the analysis, 8 criteria were used to determine the location of the KJA, namely: distribution of caught tuna, salinity, temperature, dissolved oxygen, brightness, acidity, depth, and current velocity. From these 8 criteria, it was found that Sangihe waters is a very strategic area and is not at risk to be used as a location for yellowfin tuna cultivation offshore.